Eco-economic development under social constraints : how to redirect it toward sustainability? - Muñoz, Lucio (Universidad Nacional de Quilmes, 2003)
There are social limits to eco-economic growth, yet they are not actively accounted for within this new dominant paradigm. This situation has very important implications under sustainable development and sustainability. This paper has four goals: a) to call for the dropping of the term "sustainable development" from the development literature in order to allow for the clear specification and presentation of existing alternative paths toward sustainability; b) to summarize the characteristics and limits underlying the Eco-Economic Development model; c) to point out the limiting and compounding effect of social agents within this model; and d) to indicate the need to incorporate social factors as active agents in order to turn the Eco-Economic model toward Sustainability.